Phytochemical screening of Moringa oleifera leaf extracts and their antimicrobial activities - Bagheri, Gholamreza; Martorell, Miquel; Ramírez-Alarcón, Karina; Salehi, Bahare; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Moringa oleifera is a tree native to tropical and subtropical regions of South India and used in traditional medicine. The aim of this study was characterize the phytochemicals present in M. oleifera leaf extracts and study their antimicrobial activities. Solvent extractions with Soxhlet apparatus of leaves were obtained using hexane, benzene, isopropanol, methanol, and water. The crude extracts were concentrated and screened for qualitative phytochemical analysis, and the antibacterial, antifungal and antiviral activities of crude extracts were measured by in vitro methods. Alkaloids, carbohydrates, tannins, phenolic compounds, terpenoids, cardiac glycosides, amino acids, oils and fats were found in the different crude extracts analyzed. Water and methanol extracts showed antibacterial activity against all selected bacteria, hexane and benzene extracts showed antifungal activity against all fungi tested, and hexane, benzene and isopropanol extracts showed activity against Hepatitis B virus. In conclusion, the leaves of M. oleifera have antimicrobial phytochemicals.